Analysis of chaotic behaviour according to the playing lines of Iraqi Premier League football players - Radi , Karrar; Hani , Ahmed; Khudhair , Muwafaq (Journal of Physical Education, 2025)
This research aims to analyze the chaotic behaviour of Iraqi Premier League football players according to the lines of play (defense, midfield, and attack). Chaotic behaviour refers to player actions that may deviate from the expected tactics on the field, affecting team performance. In light of the increasing competition in the Iraqi Premier League, understanding the impact of this behaviour on collective performance is essential to improving the effectiveness of team tactical plans. The research problem lies in the emergence of disorganized behaviour among Iraqi Premier League players, which directly impact team performance. These behaviours vary in their impact depending on the player’s position and line of play. The research focuses on determining whether chaotic behaviour supports creativity and changes the flow of play for the better, or whether it leads to team chaos and declining performance. The research sample was selected from Iraqi Premier League players, including players from various lines of play: defence, midfield, and attack. Players were divided according to their positions on the field to analyse their behaviour in matches. The study relied on an analysis of league matches using questionnaires to measure psychological and physical factors associated with disruptive behaviour. The disruptive behaviour were categorized and their impact on the team’s tactical plans was determined. The results revealed that chaotic behaviour varied from one line to another. Its negative impact was most evident in defence, where it led to errors and an increase in goals conceded. In midfield, the effect was twofold, as it sometimes facilitated creativity and positive interaction with the game. In attack, chaotic behaviour was beneficial in creating unexpected new scoring opportunities. The study recommends developing training programs that target reducing chaotic behaviour in defence and promoting it in attack in positive ways. It also recommends using continuous analysis of player performance to identify and address unhelpful chaotic patterns, while enhancing the ability to innovate on the field within a controlled tactical framework.